Predicting long‐term weight loss maintenance in previously overweight women: A signal detection approach. (10th April 2015) - Santos, Inês; Mata, Jutta; Silva, Marlene N.; Sardinha, Luís B.; Teixeira, Pedro J.
<x xml:space="preserve">Abstract</x> Objective Examine psychological and behavioral predictors of 3‐year weight loss maintenance in women. Methods Participants were 154 women in a 1‐year randomized controlled trial on weight management with a 2‐year follow‐up. Signal detection analyses identified behavioral and psychological variables that best predicted 5% and 10% weight loss at 3 years. Results Women with better body image were more likely to have lost ≥5% weight at 3 years (P < 0.001). Exercise intrinsic motivation had a partial compensatory effect, in that women with poor body image but higher motivation were more likely to maintain weight loss than women with poor body image and lower motivation (P < 0.001). Women with high exercise autonomous motivation were three times more likely to have lost ≥10% weight than were those with lower autonomous motivation (P < 0.001). Among women with lower autonomous motivation, perceiving fewer exercise barriers was somewhat compensatory: these women were more likely to maintain weight loss than women with lower autonomy but more perceived barriers (P < 0.01). Conclusions In overweight women, improving body image and increasing autonomous and intrinsic motivation for exercise likely promotes clinically significant long‐term weight loss maintenance. Decreasing perceived exercise barriers is another promising intervention target.